Development of intensity based fog climatological information system (daily and hourly) at IGI airport, New Delhi for use in fog forecasting and aviation (MAUSAM, 2012)
The main objective of the present paper is to make a microclimatological study of occurrence of fog of different intensities at Indira Gandhi International (IGI) airport, New Delhi which includes their date-wise climatological probabilities and their corresponding total number of hours of occurrence for 62-days of peak winter from 1st December to 31st January by using hourly visibility data for the period of 1981-2005. Their hourly climatology has been discussed separately for both months using same data for understanding their diurnal variations. Both the computations have been done to find most vulnerable periods with exact dates and timings when both duration and intensity of the fog are very high and hazardous for aviation. Corresponding 10-days and 3-hourly climatology of cumulative fog occurrences are computed to identify a period when fog related flight diversion risk is highest. For better understanding of their variability, dates of extreme hours of occurrences of a particular fog type amongst occurrences of all dates for the period during both months have also been documented. These climatological informations can be used by various airlines for planning flight operation and action for establishment of fog dissipation mechanism. Finally, fogprobability matrices of various intensities based on these climatological data have been presented with dates in first column and hours in the first row for all 62 days of December and January and for all 24 hours of each day giving date and hour wise climatological probability of their occurrences which can be used at IGI as climatological tool for forecasting of fog of various intensity and expected climatological period.